Effects of consecutive domestic and international tournaments on heart rate variability in an elite rugby sevens team - Flatt, A. A.; Howells, D.; Williams, S. (Journal of Science and Medicine in Sport, 2019)
Objectives: The purpose of this study was to evaluate heart rate variability and athlete self-report measures of recovery status (ASRM) in response to consecutive domestic and international tournaments among an elite rugby sevens team. Design: Retrospective. Methods: Olympic-level rugby sevens players (n = 10) recorded post-waking natural logarithm of the root mean square of successive differences (LnRMSSD) and ASRM (sleep quality, energy, soreness, recovery and mood) throughout a 1-week baseline period and daily thereafter throughout a domestic and subsequent international tournament, separated by five days. Linear mixed models and Hedge`s effect sizes ± 95% confidence interval (ES ± 95% CI) were used to evaluate variation in LnRMSSD and ASRM relative to baseline. Results: Decrements in various ASRM were observed in response to both tournaments (ES = -0.80 ± 0.91 to -1.73 ± 1.03, p < 0.05) and international travel (ES = -1.03 ± 0.93 to -1.70 ± 1.02, p < 0.05) whereas decrements in LnRMSSD were only observed in response to the international tournament (ES = -0.89 ± 0.92 to -1.21 ± 0.96, p = 0.02-0.07). No clear differences in internal or external match-load parameters were observed between tournaments (ES = -0.35 ± 0.88 to 0.13 ± 0.88, p > 0.05). Conclusions: Greater decrements in cardiac-autonomic activity were observed in response to an international tournament relative to a domestic tournament, despite no difference in match-physical demands. Thus, factors separate from competition alone may impact players` cardiac-autonomic response to an international tournament.